Impact of Irpex lenis and Schizophyllum commune endophytic fungi on Perilla frutescens: enhancing nutritional uptake, phytochemicals, and antioxidant potential - Sharma, Kiran; Verma, Rachna; Kumar, Dinesh; Kumar, Vinod (Springer, 2024)
Background: Endophytic fungi (EF) reside within plants without causing harm and provide benefits such as enhancing nutrients and producing bioactive compounds, which improve the medicinal properties of host plants. Selecting plants with established medicinal properties for studying EF is important, as it allows a deeper understanding of their influence. Therefore, the study aimed to investigate the impact of EF after inoculating the medicinal plant Perilla frutescens, specifically focusing on their role in enhancing medicinal properties. Results: In the current study, the impact of two EF i.e., Irpex lenis and Schizophyllum commune isolated from A. bracteosa was observed on plant Perilla frutescens leaves after inoculation. Plants were divided into four groups i.e., group A: the control group, group B: inoculated with I. lenis; group C: inoculated with S. commune and group D: inoculated with both the EF. Inoculation impact of I. lenis showed an increase in the concentration of chlorophyll a (5.32 mg/g), chlorophyll b (4.46 mg/g), total chlorophyll content (9.78 mg/g), protein (68.517 ± 0.77 mg/g), carbohydrates (137.886 ± 13.71 mg/g), and crude fiber (3.333 ± 0.37%). Furthermore, the plants inoculated with I. lenis showed the highest concentrations of P (14605 mg/kg), Mg (4964.320 mg/kg), Ca (27389.400 mg/kg), and Mn (86.883 mg/kg). The results of the phytochemical analysis also indicated an increased content of total flavonoids (2.347 mg/g), phenols (3.086 mg/g), tannins (3.902 mg/g), and alkaloids (1.037 mg/g) in the leaf extract of P. frutescens inoculated with I. lenis. Thus, overall the best results of inoculation were observed in Group B i.e. inoculated with I. lenis. GC-MS analysis of methanol leaf extract showed ten bioactive constituents, including 9-Octadecenoic acid (Z)-, methyl ester, and hexadecanoic acid, methyl ester as major constituents found in all the groups of P. frutescens leaves. The phenol (gallic acid) and flavonoids (rutin, kaempferol, and quercetin) were also observed to increase after inoculation by HPTLC analysis. The enhancement in the phytochemical content was co-related with improved anti-oxidant potential which was analyzed by DPPH (% Inhibition: 83.45 µg/ml) and FRAP (2.980 µM Fe (II) equivalent) assay as compared with the control group. Conclusion: Inoculation with I. lenis significantly enhances the uptake of nutritional constituents, phytochemicals, and antioxidant properties in P. frutescens, suggesting its potential to boost the therapeutic properties of host plants. Graphical Abstract: (Figure presented.)
Keywords: Endophytic fungi; Isolation; Inoculation; Gene sequencing; Nutrient up-take; Phytoconstituent profiling; 3107 Microbiology; 31 Biological Sciences; Nutrition; Complementary and Integrative Health; Dietary Supplements; Biotechnology; Perilla frutescens; Antioxidants; Schizophyllum; Phytochemicals; Endophytes; Plant Leaves; Chlorophyll; Schizophyllum